PENGARUH KOMPOSISI GELATIN-KARBONAT APATIT TERHADAP KEMAMPUAN GELATIN-KARBONAT APATIT MEMUAT (LOADING) SINAMALDEHIDA - , WILVIA; , drg. Anne Handrini Dewi, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the cinnamon ingredients is cinnamaldehyde, which has anti- inflammatory effect. In oral application, cinnamaldehyde will be quite soluble due to its low molecular weight. For that, drug carrier such as gelatin is needed. Carbonated apatite (CHA) is one of a material that is used to support the regeneration of hard tissue. The aim of this study was to investigate the effect of different compositions of gelatin-CHA to the ability of gelatin-CHA to load the cinnamaldehyde. The composition of gelatin-CHA membranes used in this study was varied. The membranes were soaked in the solution of cinnamaldehyde with 4% concentration for 30 minutes dan removed. The remaining solution was measured by using a spectrophotometer with 291nm wave length. Absorbance values obtained were converted to loading percentage and analyzed. Results of One Way Anova test mostly showed the significance value of <0,05 so that it is concluded that there is an effect of different composition of gelatin-CHA to the ability of gelatin-CHA to load cinnamaldehyde.